Pain Behaviour Scale (PaBS): An Exploratory Study of Reliability and Construct Validity in a Chronic Low Back Pain Population - Dalyah M. Alamam; Andrew Leaver; Niamh Moloney; Hana I. Alsobayel; Ghada Alashaikh; Martin G. Mackey (Pain Research and Management)
Objectives. To examine the interrater and intrarater reliability and construct validity of the Pain Behaviour Scale during standard physical performance tests in people with chronic low back pain and to confirm the test-retest reliability of the physical performance tests in this population. The Pain Behaviour Scale (PaBS) is an observational scale that was recently designed to uniquely measure both the presence and severity of observed pain behaviours. Methods. Twenty-two participants with chronic low back pain were observed during performance of five physical performance tests by two raters. Pain behaviours were assessed using the Pain Behaviour Scale. The Visual Analogue Scale and Modified Oswestry Disability Index were used to measure pain and disability, respectively. Descriptive statistics were used to report demographic features of participants. Reliability was analyzed using ICCs. Rater agreement was analyzed using the weighted Cohen’s kappa. Correlations between PaBS, self-reported measures, and physical performance tests were calculated using Pearson’s product-moment correlations. Results. The PaBS demonstrated excellent interrater (ICC2,1 = 1.0, 95% CI: 0.9 to 1.0) and intrarater (ICC3,1 = 0.9, 95% CI: 0.8 to 1.0) reliability. Component physical performance tests (i.e., time and distance) demonstrated good test-retest (0.6–1.0) reliability. Perfect agreement in the reporting of pain behaviours was found (95–100%). Correlations between pain behaviour severity and pain intensity (r = 0.6) and disability (r = 0.6) were moderate. Moderate correlations were found between pain behaviours and physical performance tests in sit to stand (r = 0.5), trunk flexion (r = 0.4), timed up and go (r = 0.4), and 50-foot walk (r = 0.4). Conclusion. The Pain Behaviour Scale is a valid and reliable tool for measuring the presence and severity of pain behaviour, and the physical performance tests are reliable tests.